Comprehensive statistical study of 452 BRCA1 missense substitutions with classification of eight recurrent substitutions as neutral. Issue 4 (13th July 2005) - Tavtigian, S V; Deffenbaugh, A M; Yin, L; Judkins, T; Scholl, T; Samollow, P B; de Silva, D; Zharkikh, A; Thomas, A
Abstract : Background: Genetic testing for hereditary cancer syndromes contributes to the medical management of patients who may be at increased risk of one or more cancers. BRCA1 and BRCA2 testing for hereditary breast and ovarian cancer is one such widely used test. However, clinical testing methods with high sensitivity for deleterious mutations in these genes also detect many unclassified variants, primarily missense substitutions. Methods: We developed an extension of the Grantham difference, called A-GVGD, to score missense substitutions against the range of variation present at their position in a multiple sequence alignment. Combining two methods, co-occurrence of unclassified variants with clearly deleterious mutations and A-GVGD, we analysed most of the missense substitutions observed in BRCA1. Results: A-GVGD was able to resolve known neutral and deleterious missense substitutions into distinct sets. Additionally, eight previously unclassified BRCA1 missense substitutions observed in trans with one or more deleterious mutations, and within the cross-species range of variation observed at their position in the protein, are now classified as neutral. Discussion: The methods combined here can classify as neutral about 50% of missense substitutions that have been observed with two or more clearly deleterious mutations. Furthermore, odds ratios estimated for sets of substitutions grouped by A-GVGD scores are consistent with the hypothesis that most unclassified substitutions that are within the cross-species range of variation at their position in BRCA1 are also neutral. For most of these, clinical reclassification will require integrated application of other methods such as pooled family histories, segregation analysis, or validated functional assay.